2019
DOI: 10.1016/j.redox.2018.101079
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Sco proteins are involved in oxidative stress defense

Abstract: Members of the evolutionary conserved Sco protein family have been intensively studied regarding their role in the assembly of the mitochondrial cytochrome c oxidase. However, experimental and structural data, specifically the presence of a thioredoxin-like fold, suggest that Sco proteins may also play a role in redox homeostasis.In our study, we addressed this putative function of Sco proteins using Saccharomyces cerevisiae as a model system. Like many eukaryotes, this yeast possesses two SCO homologs (SCO1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Of note, endothelial cells consume a slight amount of oxygen to produce ATP in order to transfer most of the oxygen to myocardium [45,46]. In vitro data suggest superoxide generated by mitochondria accounts for 0.2-2% of cellular oxygen consumption [47,48]. It has been found that endothelial cell dysfunction affects the diffusion rate of oxygen across the arteriolar vessel wall [49,50]; however, these observations require further discussion.…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Of note, endothelial cells consume a slight amount of oxygen to produce ATP in order to transfer most of the oxygen to myocardium [45,46]. In vitro data suggest superoxide generated by mitochondria accounts for 0.2-2% of cellular oxygen consumption [47,48]. It has been found that endothelial cell dysfunction affects the diffusion rate of oxygen across the arteriolar vessel wall [49,50]; however, these observations require further discussion.…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…To these we The precise functional differentiation between Sco1 and Sco2 in different species remains unknown despite various direct experimental studies [52,53,54]. New evidence suggests that they may have "distinct antioxidant capacity" in addition to their partially redundant roles in cytochrome c oxidase assembly [55]. Both are localized to the mitochondrion, but their specific location within the mitochondrial matrix could be different as a consequence of the indels in the target sequence and matrix region.…”
Section: Recurrent Sequence Evolution Reveals Evolutionary Constraintsmentioning
confidence: 98%
“…Azoramide reduces the increase in ROS and ameliorates the decline in mitochondrial membrane potential in PLA2G6 D331Y/D331Y midbrain DA neurons Oxidative stress causes the release of cytochrome c from mitochondria, which activates the apoptotic pathway [21][22][23][24][25] . Intracellular ROS in DA neurons was measured with the fluorescent probe CellROX® Green Reagent.…”
Section: Azoramide Attenuates Loss Of Pla2g6 D331y/d331y Ipscderived mentioning
confidence: 99%